(untitled) (Update Dental College Journal, 2014)
Background: Nonsquamous cell malignant tumors of jaw and oral soft tissue are rare constituting between 6%-10% of all malignancies in the region. A few case reports of individual tumors are available while reviews of significant series is lacking. This report presents 22 cases of Nonsquamous cell malignant tumors collected over 8 months at a tertiary oral care centre in Dhaka, Bangladesh. Objective: To find out the distribution & pattern of oral nonsquamous cell malignant tumors among all oral malignancy and to find out the age, sex, site, clinical presentation, the histological types of these tumors. Method: This descriptive cross sectional study was done in Oral and Maxillofacial Surgery Department, Dhaka Dental College and Hospital.The entire patient histopathologically diagnosed as any type of Nonsquamous cell tumor were selected. Data were collected in a summarized data sheet. Then histopathological types of them were analyzed to indicate the distribution according to age, gender, site and clinical presentation. Result: There were 107 Oral malignancies of which 22(20.56%) were Nonsquamous cell malignant tumors which is significant in comparison to Squamous cell carcinoma in Bangladesh. Among the respondents, 9(40.91%) were diagnosed as minor salivary glands malignant tumors, 7(31.2%) were diagnosed as sarcomas, Malignant melanoma were 4(18.18%) and Non- Hodgkins lymphoma were 2(9.09%). The male to female ratio was 1:1.2 with ages were between 9 years to 70 years old (mean age 35.45 ± 21.76 years) with most patients (36.36%) in 16 to 30 years of life. Cases presented with symptoms such as swelling (100%), pain, paresthesia, loose tooth and tissue ulceration. Conclusion: In Dhaka Dental College Hospital, nonsquamous cell malignant tumors account for 20.56% of all oral malignancies among them minor salivary glands malignant neoplasm and malignant melanoma were the predominant type. Most affected were people in the 2nd and 3rd decades of life with no sex predilection. Most common site of involvement was maxilla. The need for improved medical awareness, diagnostic facilities and upgrading of infrastructure was stressed. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17997 Update Dent. Coll. j: 2013; 3 (2): 34-38